Effects of a labour and delivery simulated practice programme for elderly primigravidas - Chun hee Seong; Kyung min Park; Kyoung ja Moon (Wiley, 2020)
Abstract Aim Increasing numbers of older gravidas compel research into best practices for their labour‐related outcomes. Responding to this need, this study sought to develop and evaluate a programme for older primigravidas. Design The authors developed a simulated practice programme for older primigravidas and tested its effects. Methods A non‐equivalent control group pre‐ and post‐test design was used with 49 community‐dwelling primigravidas. The programme taught the stages of labour using a realistic scenario‐based practice and a debriefing session. Data were collected between June and September 2015. Participants were divided into intervention (N = 25) and control (N = 24) groups. Postintervention group effects were analysed with independent t tests. Results The intervention group's levels of anxiety and stress decreased and their knowledge and self‐confidence increased. The intervention group's labour duration was also shorter than that of the control group.